Residual tumor and primary debulking surgery vs interval debulking surgery in stage IV epithelial ovarian cancer - Sarah Mejer Sørensen; Claus Høgdall; Berit Jul Mosgaard; Maya Isabella Riise Dalgaard; Mai Partridge Jensen; Katrine Fuglsang; Tine Henrichsen Schnack (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction It is debated whether women with FIGO (International Federation of Gynecology and Obstetrics) Stage IV epithelial ovarian cancer should be offered primary debulking surgery (PDS) or interval debulking surgery (IDS). Furthermore, the impact of complete resection of intra‐abdominal disease (R0) despite their extra‐abdominal metastases is questioned. The objective of this study was to investigate the impact of intra‐abdominal residual tumor, Stage IVA vs IVB, the localization and number of metastases defining Stage IV disease on overall survival (OS) comparing PDS and IDS in FIGO Stage IV epithelial ovarian cancer. Material and Methods We included 2091 women registered with Stage IIIC–IV ovarian cancer in the Danish Gynecological Cancer Database during 2009–2016. The impact of residual tumor was evaluated using univariate and multivariate analyses. Results In total, 681 patients had stage IV disease, of whom 26% underwent PDS, 38% IDS, and 36% chemotherapy only. Overall survival for PDS and IDS were similar. Patients achieving R0 at PDS showed a tendency towards a higher OS than patients achieving R0 at IDS, though the difference was non‐significant. In women with Stage IVA and IVB disease there was a survival benefit in achieving R0 both when treated with PDS and IDS. Women with Stage IVB disease treated with chemotherapy only had a significantly lower OS than patients achieving R0 at both PDS and IDS. Malignant pleural effusion and having five metastatic sites compared with having one was associated with a poorer OS. Conclusions Our study shows similar OS in patients with Stage IV disease treated with IDS compared with PDS. Complete intra‐abdominal tumor resection improves the prognosis in both PDS and IDS in Stage IV ovarian cancer. Malignant pleural effusion seems to be a negative prognostic factor and should have more focus in future studies.